2013
DOI: 10.1007/s10517-013-2021-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hepatoprotective Activity of Water-Soluble Polysaccharide Fraction of Stellaria Media L.

Abstract: Therapy of rats with CCl4 hepatitis with Stellaria media L. water-soluble polysaccharide fraction in a dose of 100 mg/kg reduces serum activities of transaminases (ALT and AST), alkaline phosphatase, bilirubin, and the thymol test values. In the liver, the density of inflammatory infiltration of the organ parenchyma, total count of necrotic hepatocytes, fatty and protein degeneration are reducing. Hence, water-soluble polysaccharide fraction, isolated from the terrestrial part of Stellaria media L., is charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 2 publications
0
3
1
Order By: Relevance
“…High levels of ALT have been attributed to the damaged structural integrity of the liver. Contrary to the findings of this study, Gorina et al [23] reported a decrease in serum activities of transaminases and bilirubin concentration in rats treated with water soluble polysaccharide fraction of S. media against CCl 4 induced hepatitis. Higher levels of globulin were observed in treated rats compared with the control group.…”
Section: Stellaria Mediacontrasting
confidence: 99%
“…High levels of ALT have been attributed to the damaged structural integrity of the liver. Contrary to the findings of this study, Gorina et al [23] reported a decrease in serum activities of transaminases and bilirubin concentration in rats treated with water soluble polysaccharide fraction of S. media against CCl 4 induced hepatitis. Higher levels of globulin were observed in treated rats compared with the control group.…”
Section: Stellaria Mediacontrasting
confidence: 99%
“…Elevated AST level in the blood is often considered as a sign of liver damage; however, AST is not specific for the liver and may be also increased due to injuries of the heart, muscle, pancreas, kidney, or red blood cells [24]. Interestingly, SM treatment actually was found to be hepatoprotective in a liver toxicity model [25]. Overall these data suggest that Stellaria media treatment has no deleterious effect on liver function; however, a possible limitation of our study is the lack of a group receiving herbal treatment without cholesterolenriched chow.…”
Section: Discussionmentioning
confidence: 99%
“…Sugarapple (Annona squamosa) (L.) [37], Madagascan Periwinkle (Cateranthus roseus) (L.) [38], tumba (Citrullus colocynthis) (L.) [39], miracle leaf (Kalanchoe pinnata) (Lam.) [40], bitter ground (Momordica charantia) [41], thai eggplant (Solanum xanthocarpum) [42], and curry leaves (Murraya koeningii) [43] are used to treat diabetes.…”
Section: Diabetesmentioning
confidence: 99%